Modeling The Influence of Project Manager Trustworthy Leadership Behavior Upon Construction Team Trust - Andi Andi; Herry Santoso; Jonathan Simanjuntak (Civil Engineering Dimension, 2008)
Appropriate trust and leadership have been frequently cited as key answer to the problems of cooperation and coordination in contractor’s teamwork. The objectives of this paper are to measure trust level of construction projects team, to investigate trustworthy leadership behavior of project managers, and to model the influence of project managers’ trustworthy leadership behavior upon team trust level. Sixty-one respondents from nine on-going construction projects participated in the questionnaire survey. The analyses show that in general the levels of trust and project managers’ trustworthy leadership behavior are medium (scores of 82.71 and 102.09 respectively). Meanwhile the positive influence of project managers’ trustworthy leadership behavior upon team trust level, modeled through multiple regression analysis with one dependent variable (i.e. trust) and three independent variables (i.e. leadership-results, leadership-integrity, and leadership-concern), is found to be significant. The model is evaluated and validated; the results reveal that the prediction of the model is satisfactory.